Causality between sarcopenia and diabetic nephropathy: a bidirectional Mendelian randomization study - Ren, Linan; Wang, Yao; Ju, Feng; Sun, Meixin; Gang, Xiaokun; Wang, Guixia (Frontiers in Endocrinology, 2023)
Background and purpose Observational studies have shown that sarcopenia is closely associated with diabetic nephropathy (DN), but the causal relationship is uncertain. This study aims to address this issue using a bidirectional Mendelian randomization (MR) study. Methodology We conducted a bidirectional MR study with data from genome-wide association studies (GWAS) including appendicular lean mass (n = 244,730), grip strength (Right: n = 461,089, Left: n = 461026), walking speed (n = 459,915), and DN (3283 cases and 181,704 controls). To assess the causality of sarcopenia on the risk of DN from the genetic perspective, we conducted Forward MR analysis with appendicular lean mass, grip strength, and walking speed as exposure and DN as outcome. Then, we performed Reverse MR analysis with DN as the outcome to detect the causality of DN on appendicular lean mass, grip strength, and walking speed. Additionally, a series of sensitivity analyses, including heterogeneity tests, pleiotropy evaluations, and Leave-one-out analyses, were conducted to test the reliability of the MR analysis results. Results Forward MR analysis showed genetically predicted appendicular lean mass loss is associated with DN risk (IVW: OR = 0.863, 95% CI 0.767 - 0.971; P = 0.014). Reverse MR showed that the development of DN was associated with a decrease in grip strength (IVW: Right β=0.003, 95% CI: -0.021 to -0.009, P=5.116e-06; Left β=0.003, 95% CI: -0.024 to -0.012, P=7.035e-09). However, the results of the other MR analyses were not statistically different. Conclusion Notably, we conclude that there is no cause and effect of between sarcopenia and DN, which suggests that sarcopenia cannot be directly contribute to the development of DN, in turn, the DN is not directly involved in the development of sarcopenia. Therefore, it seems infeasible to predict the development of DN by assessing muscle mass.